Synthesis and characterization of nano-sized aluminium oxide and its application in the fabrication of polyaniline-alumina nan - Teoh, Geik Ling (2006)
Fibrillar alumina nanoparticles of high aspect ratio with diameter of around 2 nm and length of about 70 nm have been successfully fabricated in bulk quantities for the first time via sol-gel process. In the course of preparation, the influences of the hydrolysis period, aging temperature, pH, the reactant molecular ratio and the type of solvent on the formation of area, pore volume and the pore diameter of calcined alumina determined by nitrogen experiments were XX SYNTHESIS AND CHARACTERIZATIONS OF NANO-SIZED ALUMINIUM OXIDE AND ITS APPLICATION IN THE FABRICATION OF POLYANILINE-ALUMINA NANOFIBERS 27AI alumina nanofibers were illustrated. Morphological studies were performed by TEM. The effects of various calcination temperatures on the phase transformation of AI2O3 were also demonstrated. The as-prepared sample gave amorphous phase assigned as pseudoboehmite, which was entirely converted into a-AI2O3 by calcination at 1050 °C for 5 h as verified by XRD patterns. The BET surface adsorption-desorption a function of the calcination temperature. Specific surface areas as high as 335 m2/g were exhibited by the calcined solids at 540 °C. Molecular characterizations were also perfomed by FTIR and MAS NMR spectroscopy. Thermal behavior of alumina nanofibers was investigated by TGA and DSC.